Kontribusi Sosiologi Dakwah dalam Menghadapi Generasi Milenial: Contribution of the Sociology of Da'wah in Facing the Millennial Generation - Ridwan, Ridwan; Mahmuddin (DIRASAH: Jurnal Kajian Islam, 2025)
The rapid development of the digital era has significantly influenced the mindset, behavior, and daily lives of the millennial generation, who are often referred to as "digital natives." This phenomenon presents both challenges and opportunities for Islamic preaching (dakwah). Traditional methods, such as lectures or conventional study circles, often fail to resonate with millennials. They demand interactive, technology-based approaches that align with their lifestyles and values, including inclusivity, freedom of expression, and concern for global issues. Sociology of dakwah plays a strategic role in addressing these challenges by analyzing the social dynamics and unique characteristics of millennials. It provides insights into their dependence on technology, digital communication patterns, and values, enabling the formulation of effective preaching methods. Leveraging social media and digital technology, preachers can creatively and contextually deliver Islamic messages while addressing contemporary issues such as environmental sustainability, social justice, and inclusivity. This study employs a qualitative descriptive-analytical approach to explore the contribution of the sociology of dakwah in applying relevant methods for preaching to millennials. Additionally, it identifies challenges such as hedonism, instant gratification, and individualism, and proposes strategies to overcome these obstacles. By integrating innovative and interactive approaches, dakwah can effectively address the spiritual and intellectual needs of millennials, ensuring the message of Islam remains relevant in the modern era.